The Role of 3D Printing in Revolutionizing Pharmaceuticals and Medicine - Singh, Reena; Wani, Atif Khurshid; Peter, Lukas; Randlova, Kristina; Hruska, Jan; Chopra, Chirag; Kuca, Kamil (Mini Reviews in Medicinal Chemistry, 2025)
Three-dimensional (3D) printing is a transformative technology that has significantly influenced multiple sectors, including aviation, defence, architecture, and, more recently, healthcare and pharmaceuticals. Despite its growing adoption, there remain gaps in consolidated knowledge regarding its material versatility, regulatory considerations, and real-world implementation in clinical and pharmaceutical settings. Challenges related to biocompatibility, scalability, and the standardization of printed products hinder its full integration into medical practice. Addressing these issues requires a comprehensive understanding of the technological foundation, materials, and evolving applications of 3D printing in medicine. This review aims to provide an in-depth analysis of current advances, limitations, and prospects of 3D printing in healthcare. A systematic literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar databases, focusing on peer-reviewed articles published between 2010 and 2024. The review highlights key fabrication techniques, material innovations, clinical applications, and integration with emerging technologies, addressing critical challenges and opportunities for advancing personalized medicine.
Keywords: fabricating materials